2002
DOI: 10.1046/j.1471-8286.2002.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of simple sequence repeat (SSR) markers for the assessment of gene flow between sea beet (Beta vulgaris ssp. maritima) populations

Abstract: Molecular markers can be used to estimate gene flow indirectly by monitoring the relative frequency of alleles in adjacent populations. Sea beet (Beta vulgaris ssp. maritima) is a wild plant species found along the coastlines of many European countries and is closely related to cultivated beets. A set of six simple sequence repeat (SSR) markers that are polymorphic in UK populations have been developed for sea beet to assess the problems of indirect measurement of gene flow in these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 14 publications
2
9
0
1
Order By: Relevance
“…H values ranged from 0.12-0.90, with an average value of 0.57 (table 2). These values are similar to those observed previously in quinoa (Mason et al 2005) as well as in related species such as sugar beet (Beta vulgaris L.) (Rae et al 2000;Cureton et al 2002). According to Ott (1992), a marker is considered polymorphic if H≥0.10 and highly polymorphic if H≥0.70.…”
Section: Ssr Discovery and Analysissupporting
confidence: 86%
“…H values ranged from 0.12-0.90, with an average value of 0.57 (table 2). These values are similar to those observed previously in quinoa (Mason et al 2005) as well as in related species such as sugar beet (Beta vulgaris L.) (Rae et al 2000;Cureton et al 2002). According to Ott (1992), a marker is considered polymorphic if H≥0.10 and highly polymorphic if H≥0.70.…”
Section: Ssr Discovery and Analysissupporting
confidence: 86%
“…The SSR markers reported in this study add to the four genomic SSR markers developed by Mörchen et al (1996), 57 genomic, restricted‐use SSRs developed by Rae et al (2000), 11 genome‐based SSR markers developed from sea beet ( B. vulgaris spp. maritima ; Cureton et al, 2002; Viard et al, 2002), eight genomic SSR markers developed by Richards et al (2004), 23 newly reported SSR markers used for mapping purposes by McGrath et al (2007), 25 genomic SSR markers developed by Smulders et al (2010), 13 EST‐based SSR markers reported in Simko et al (2012), and the 242 genomic SSRs and 773 EST‐based SSRs reported by Laurent et al (2007), of which 41 genomic SSR marker primer pairs were published.…”
Section: Resultsmentioning
confidence: 99%
“…maritima that is not captured in the cultivated crops. Molecular markers have been used extensively to characterize sugar beet and related Beta species (Jung and Herrmann, 1991;Mita et al, 1991;Jung et al, 1993;Senda et al, 1995;Kraft et al, 1997;Shen et al, 1998;McGrath et al, 1999;Wang and Goldman, 1999;Kraft et al, 2000;Cureton et al, 2002;Richards et al, 2004;Poulsen et al, 2007;Fénart et al, 2008). Genetic diversity in cultivated beets is low compared with other beet types , and cultivated beets may contain only a quarter to a third of the genetic diversity present in sea beets (Fénart et al, 2008;Saccomani et al, 2009).…”
Section: Genetic Mapsmentioning
confidence: 99%